2000
DOI: 10.1016/s0370-2693(00)00908-4
|View full text |Cite
|
Sign up to set email alerts
|

The α-particle in nuclear matter

Abstract: Among the light nuclear clusters the α-particle is by far the strongest bound system and therefore expected to play a significant role in the dynamics of nuclei and the phases of nuclear matter. To systematically study the properties of the α-particle we have derived an effective four-body equation of the Alt-Grassberger-Sandhas (AGS) type that includes the dominant medium effects, i.e. self energy corrections and Pauli-blocking in a consistent way. The equation is solved utilizing the energy dependent pole ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 22 publications
5
95
0
Order By: Relevance
“…In the limit of small-amplitude fluctuations ρ = ρ 0 + δρ, Eqs. (16)(17) can be transformed into a diffusion equation:…”
Section: B Hydrodynamical Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the limit of small-amplitude fluctuations ρ = ρ 0 + δρ, Eqs. (16)(17) can be transformed into a diffusion equation:…”
Section: B Hydrodynamical Evolutionmentioning
confidence: 99%
“…It is predicted to lead to the presence of complex structures like the "pasta phases" occurring in the inner crust of neutron stars [11,12,13,14]. At lower densities and finite temperature, star matter may clusterize into light nuclei [15,16]. Around the core of supernovae, density fluctuations could have important effects on neutrino propagation [17], which is crucial for the description of supernova dynamics [18].…”
Section: Introductionmentioning
confidence: 99%
“…[18]. Thus, the state has been proposed to be related to boson condensation of α particles in infinite nuclear matter [19][20][21]. The new interpretation of the Hoyle state as an α condensate has provoked many theoretical and experimental works on α-particle condensation phenomena in light nuclei [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The effective wave equation has been solved using separable potentials for A = 2 by integration. For A = 3, 4 we can use a Faddeev approach [7]. The shifts of binding energy can also be calculated approximately via perturbation theory.…”
Section: Nuclear Clusters In the Mediummentioning
confidence: 99%
“…(2), the effect of the medium on the properties of an α particle in meanfield approximation (i.e., for an uncorrelated medium) is produced by the Hartree-Fock self-energy shift and Pauli blocking. The shift of the α-like bound state has been calculated using perturbation theory [8] as well as by solution of the Faddeev-Yakubovski equation [7]. It is found that the bound states of clusters d, t, and h with A < 4 are already dissolved at a Mott density ρ Mott α ≈ ρ 0 /10, see Fig.…”
Section: Nuclear Clusters In the Mediummentioning
confidence: 99%